Evaluation of the Sustainability of the Essential Public Health Effort Program at the Team-based Nusantara Sehat Assignment Health Center, Ministry of Health, Republic of Indonesia - waris, lukman; Arifiati, Nurce; Hendarwan, Harimat; Siswati , Tri (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
Background: The Nusantara Sehat Team-based Program (NST) is a program that places health workers with 9 categories of health professionals in remote border areas and islands (DTPK) for 2 years every batch. NST aims to fill the shortage of health workers at the DTPK puskesmas so that the main tasks of the puskesmas can continue. This study aims to evaluate the sustainability of the essential public health program at the NST placement center between 2016 and 2018. Method: Quantitative research method with cross-sectional design. The population is the NST batch 1-2 community health center (2016) as post-placement and NST batch 6-8 health center (2018) as placed in 28 provinces, 43 districts, and 39 health centers. The sample is the community at the placement and post-placement health centers. Data collection was carried out by interviewing the people who were selected as samples using a questionnaire by trained enumerators. A statistical test was conducted to assess the average coverage index of the essential public health program at the puskesmas by comparing the average coverage index of the program during placement and after placement with an independent t-test. The result: The results of the study showed that the NST essential public health program experienced sustainability, as seen from the results of statistical analysis, it was found that p = 0.26 95% CI (0.11-0.41) at the NST placement health center and p = 0.76 95% CI (0.36-0.49) at post-placement health centers. Sustainable programs are health promotion, empowerment, environmental health, MCH, and Nutrition. Programs that are not sustainable are disease prevention